Enteric-Coated Aspirin Induces Small Intestinal Injury via the Nrf2/Gpx4 Pathway: A Promising Model for Chronic Enteropathy - Zhang M; Xia S; Feng L; Han X; Zhang Y; Huang Y; Liu Y; Zhao K; Guan J; Tian D; Liao J; Yu Y (Drug Design, Development and Therapy)
Mingyu Zhang, Suhong Xia, Lina Feng, Xu Han, Yu Zhang, Yujie Huang, Yiran Liu, Kai Zhao, Jialun Guan, Dean Tian, Jiazhi Liao, Yan Yu Department of Gastroenterology, Tongji Hospital of Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei Province, 430030, People’s Republic of ChinaCorrespondence: Jiazhi Liao, Email liaojiazhi@tjh.tjmu.edu.cn; Yan Yu, Email whtj20200720@163.comBackground: Aspirin is widely used to prevent and treat cardiovascular diseases. The most common side effect is gastrointestinal damage. In recent years, aspirin-associated enteropathy has received increasing attention. This study aimed to establish a chronic model of aspirin-associated enteropathy, investigate the effect of enteric-coated aspirin on the intestinal flora, and explore the specific molecular mechanism of small intestinal damage.Methods: C57BL/6J mice were given aspirin for 45 days to induce chronic small intestinal injury. The intestinal mucosal injury was observed macroscopically and microscopically. Intestinal mucus levels were assessed by PAS staining. The intestinal permeability was measured by FD4. The oxidative stress levels of the small intestine were detected by immunofluorescence and immunohistochemistry. The mRNA and protein levels of inflammatory factors, tight junctions, and antioxidant defense-related genes were measured by qRT-PCR and Western Blot. The MPO activity, SOD activity and MDA content in serum were measured. The mitochondrial morphology and paracellular space were observed under transmission electron microscopy. The fecal samples were analyzed by high-throughput sequencing of 16S rRNA V3-V4 amplicons.Results: Aspirin induced weight loss, reduced food intake and increased faecal occult blood in mice. Aspirin led to a shortened small intestine, macroscopic and microscopic damage to the intestinal mucosa, and local inflammation. Aspirin disrupted the intestinal barriers and increased the permeability of the small intestine. Aspirin destroyed mitochondrial structure and damaged antioxidant capacity, and aspirin may induce oxidative stress through Nrf2/Gpx4 signaling pathway. Intestinal flora analysis showed that aspirin could induce changes in the abundance of Akkermansia and Lactobacillus.Conclusion: Long-term administration of enteric-coated aspirin successfully established a chronic small intestinal injury model in mice. It increased oxidative stress in the small intestine by disrupting mitochondrial structure and impairing antioxidant capacity. This damaged the intestinal mucosal barrier, increased intestinal permeability, and triggered gut microbial dysbiosis and inflammation. Keywords: aspirin, oxidative stress, ferroptosis, mucosal barrier disruption, enteritis